Adjustment of Anti-Hyperglycaemic Agents During Bowel Preparation for Colonoscopy in Patients with Diabetes - Müssig, Karsten; Adamek, Henning E. (Experimental and Clinical Endocrinology & Diabetes, 2022)
Objective Due to the growing diabetes pandemic, the number of colonoscopies performed in patients with diabetes is steadily rising. However, recommendations on adjustments of anti-hyperglycaemic agents (AHG) during bowel preparation for colonoscopy are limited.Methods A total of nine articles were revealed on a PubMed search using the search terms “diabetes” and “colonoscopy”, “sigmoidoscopy”, “endoscopy”, “endoscopic intervention”, “endoscopic invasive diagnostics”, “endoscopic surgery”, or “diabetes care in the hospital” and manual screening of the references of the articles reporting on AHG adjustment during bowel preparation.Results Regular glucose measurements and the opportunity to contact the diabetes team were commonly advised. Recommendations also agreed that all oral AHG and short-acting insulin should be omitted when patients are on clear fluids. Recent studies suggest discontinuation of sodium-glucose cotransporter-2 (SGLT2) inhibitors even three days before the colonoscopy. In contrast, recommendations differed regarding adjustment of basal insulin depending on diabetes type and time point in relation to the intervention.Conclusions While discontinuation of oral AHG and short-acting insulin during bowel preparation for colonoscopy is generally accepted, recommendations on the adaptation of basal insulin follow different approaches.
Keywords: Humans; sodium; glucose transporter 2 inhibitors; insulin; short-acting; adaptation; physiological; colonoscopy; PubMed; glucose